Peningkatan Kemampuan Berpikir Kritis Siswa dalam Pembelajaran IPAS Menggunakan Model Children Learning In Sciense - Rahmawati, Syafitri; Sundahry; Pitra, Dedek Helida (CV. Master Literasi Indonesia, 2025)
This study aims to improve students' critical thinking skills in Social Science (IPAS) learning through the application of the Children Learning In Science (CLIS) model. The research design used is Classroom Action Research (CAR) conducted in two cycles, where each cycle consists of planning, implementation, observation, and reflection. The subjects of this study were 13 fifth-grade elementary school students who constituted both the population and sample of the study. The object of the study focused on improving students' critical thinking skills through the CLIS learning model. Data collection techniques included observation, evaluation of critical thinking skills, and document recording, which were then examined using quantitative and descriptive qualitative approaches. The results of the study show an increase in critical thinking skills from cycle I to cycle II, with the “very critical” level increasing from 38.46% to 76.92%. The Children Learning in Science (CLIS) approach has been proven effective in facilitating the development of students' critical thinking skills in elementary science teaching.